1991
DOI: 10.1017/s0954394500000430
|View full text |Cite
|
Sign up to set email alerts
|

Marking in discourse: “Birds of a feather”

Abstract: Subject/verb agreement and subject/predicate adjective agreement in spoken Brazilian Portuguese are subject to a parallel processing effect, such that marking leads to further marking and lack of marking leads to further lack of marking. For example, semantically plural verb tokens preceded by marked plural subjects in the same clause or other marked verb tokens with the same subject in the preceding discourse are more likely to be explicitly marked for plural than similar tokens preceded by unmarked subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 3 publications
5
37
0
3
Order By: Relevance
“…Therefore, we do not claim to have found a final explanation. But we do claim to have found a psycholinguistic theory of language production which provides a coherent and reasoned account of our findings and which may also profitably apply to findings in other sociolinguistic research into perservations (Poplack 1980;Pereira Scherre 2001;Pereira Scherre & Naro 1991;and Weiner & Labov 1983).…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Therefore, we do not claim to have found a final explanation. But we do claim to have found a psycholinguistic theory of language production which provides a coherent and reasoned account of our findings and which may also profitably apply to findings in other sociolinguistic research into perservations (Poplack 1980;Pereira Scherre 2001;Pereira Scherre & Naro 1991;and Weiner & Labov 1983).…”
Section: Introductionsupporting
confidence: 69%
“…Evidence supporting this answer may be found in multiple studies within variationist sociolinguistics and within spreading-activation research in psycholinguistics which find systematic effects for what researchers have identified as priming or persistence or perseverance or perseveration or, in even more colorful terms, a "birds of a feather" effect (Pereira Scherre & Naro 1991). It is unfortunate that such multiple terms exist.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, subjects without a plural marker on the last element tend to trigger unmarked plural verbs. These effects have been described in detail in the relevant literature on Brazilian Portuguese for the last 30 years, in articles published in Language (Naro 1981), Language Variation and Change (Scherre and Naro 1991, 1992, Naro and Scherre 1996a, Scherre 2001) and in Selected Papers from NWAV 8 (Scherre 1981, Guy 1981, NWAV 23 (Naro and Scherre 1996b), NWAV 38 (Scherre and Naro 2010).…”
Section: Nonstandard Constructions Cited In the Textbookmentioning
confidence: 99%
“…Second, irregular plurals can be bare singulars, but irregular plurals cannot ''delete'' their plural morpheme. SeeSchmitt and Munn (2002) andScherre and Naro (1991) for more details.7 We leave aside any differences that may exist between the indefinite articles in Romance and the English indefinite article.…”
mentioning
confidence: 99%